NODIRA CREATIVITY AND LOVE - Karimova Nilufar Majidovna (American Journals Publishing, 2025)
This article covers the work of Nodira and artistic interpretations of Ishq in her work. The Lord of Nodira and the ghazals in him are artistically analyzed.
Keywords: Nodira, devon, literary environment, Comila, Mcnuna, zullisonain, Ghazal, ishq.